Left Politics in United States - Dr. Anurag Pandey (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Recently an attack on Donald Trump by an Youth came as a shock to the world. A huge section of world Media and Trump supporters claimed this attack as a ploy by International left. Opponents of leftist politics cited the example of recently held elections in France, Britain and India where in two countires France and Britain International left got huge success. In India international left with its narrative failed to accrue the desired result. Those who believed in this theory claim that attack on Donald Trump was an attempt to give a jolt to right.